2022
DOI: 10.1039/d1fo04420f
|View full text |Cite
|
Sign up to set email alerts
|

N-3 polyunsaturated fatty acids prevent the d-galactose-induced cognitive impairment by up-regulating the levels of 5-hydroxymethylcytosine in the mouse brain

Abstract: Decreased 5-hydroxymethylcytosine (5hmC) levels caused by mitochondrial dysfunction in brain are closely associated with the development of neurodegenerative disease. It has been reported that n-3 polyunsaturated fatty acids (PUFA) prevent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The increase in the RI was also observed in the D-Gal-induced aging rats-treated with PEP extract at doses of 250 and 500 mg/kg when compared with the aging model group; however, these differences did not show statistical significance (p > 0.05). Consistent with other studies [36,37], we found that the impairment of recognition memory was induced by D-Gal, resulting in a reduction of the RI as observed in the NOR test, while PEP extract (500 mg/kg) as well as DNP treatment abolished the amnestic effect of D-Gal.…”
Section: Effects Of Eggplant Extract On Learning and Memory Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in the RI was also observed in the D-Gal-induced aging rats-treated with PEP extract at doses of 250 and 500 mg/kg when compared with the aging model group; however, these differences did not show statistical significance (p > 0.05). Consistent with other studies [36,37], we found that the impairment of recognition memory was induced by D-Gal, resulting in a reduction of the RI as observed in the NOR test, while PEP extract (500 mg/kg) as well as DNP treatment abolished the amnestic effect of D-Gal.…”
Section: Effects Of Eggplant Extract On Learning and Memory Performancesupporting
confidence: 92%
“…However, when present at high levels, it has the potential to induce the accumulation of ROS, leading to oxidative stress and subsequent cellular damage [31]. Many studies have reported that chronic administration of D-Gal cause cognitive deficits, which are mediated through various mechanisms in the brain, including oxidative stress [32][33][34][35], inflammation [32,33,35], cholinergic dysfunction [35], mitochondrial dysfunction [34,36], AGEs accumulation [33]. The hippocampus is a complex structure within the temporal lobe.…”
Section: Effects Of Eggplant Extract On Learning and Memory Performancementioning
confidence: 99%
“…8 Edible oils are an essential part of our daily lives, and their intake plays a very important role in people's health. It has also been confirmed that the intake of oils rich in polyunsaturated fatty acids (such as walnut oil, 9 camellia oil, 10 olive oil 11 and peony seed oil 12 ) could significantly prevent and mitigate the onset of neurodegenerative diseases or neuroinflammatory conditions, including AD. 13 This is because polyunsaturated fatty acids can improve cognitive impairment or neuronal deficits by promoting neuronal growth.…”
Section: Introductionmentioning
confidence: 97%